Ketamine-induced changes in plasma brain-derived neurotrophic factor (BDNF) levels are associated with the resting-state functional connectivity of the prefrontal cortex. (20th October 2020) - Woelfer, Marie; Li, Meng; Colic, Lejla; Liebe, Thomas; Di, Xin; Biswal, Bharat; Murrough, James; Lessmann, Volkmar; Brigadski, Tanja; Walter, Martin
Abstract: Objectives: Synaptic plasticity and brain-derived neurotrophic factor (BDNF) signalling are proposed to play key roles in antidepressant drug action. Ketamine, an N-methyl-D-aspartate receptor antagonist and putative antidepressant, may increase synaptic plasticity in prefrontal cortex through higher expression of BDNF. Furthermore, ketamine was shown to change resting-state functional connectivity (RSFC) of dorsomedial prefrontal cortex (dmPFC). Methods: In a randomised, placebo-controlled study, we investigated acutely (100 min) and at 24 h following subanesthetic ketamine infusion which dmPFC seeded RSFC changes are most strongly associated with plasma BDNF level changes in 53 healthy participants (21 females, age: 24.4 ± 2.9 years) using 7 T-fMRI. Results: We observed higher relative levels of BDNF 2 h and 24 h after ketamine compared to placebo. Whole-brain regression revealed that the change in BDNF after 24 h was associated with RSFC decreases from dmPFC to posterior cingulate cortex and ventromedial PFC at 24 h and exploratively also at the 100 min measurement point. Follow-up analyses revealed that RSFC reductions following ketamine were restricted to subjects showing increased BDNF levels at 24 h. Conclusions: Our findings indicate BDNF level dynamics following ketamine are related to acute and 24 h RSFC changes. Particularly when BDNF increases are observed after ketamine infusion, a disconnection from dmPFC after 24 h is seen and may reflect synaptic plasticity effects.